Mars! : [book with audioplayer] Earthlings welcome - McAnulty, Stacy (McAnulty, Stacy. Our universe., 2021)
Meet Mars! The red planet. Planet Marvelous. Favorite sibling of Earth (or so he claims). Sometimes they're close (just 34.5 million miles apart). Sometimes they need space (250 million miles apart)! Earth and Mars have a lot in common--clouds, mountains, polar icecaps. And while Earth has Earthlings, Mars makes a persuasive case for why people should make the journey to spend time with him. His day is 7 minutes longer! He is home to the largest volcano in the whole solar system. He's, well, marvelous.